Selenium antimony sulfide thin film and preparation method and application thereof

By employing a hydrothermal reaction with a magnetic field treatment, the crystallinity of antimony selenide sulfide films is enhanced, addressing the quality issues and improving the performance of solar cells.

CN119173117APending Publication Date: 2024-12-20UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411288695.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The crystallinity of antimony selenide sulfide films in solar cells is inadequate, limiting the quality and efficiency of solar energy devices.

Method used

A method involving a hydrothermal reaction combined with a magnetic field treatment is used to prepare antimony selenide sulfide films, utilizing a precursor solution of potassium antimony tartrate, sodium thiosulfate, and selenourea, with specific parameters for temperature, magnetic field intensity, and duration to enhance crystallinity.

Benefits of technology

The method improves the crystallinity of the antimony selenide sulfide films, enhancing their grain orientation and reducing defects, thereby improving the quality and performance of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173117A_ABST
    Figure CN119173117A_ABST
Patent Text Reader

Abstract

The invention provides a selenium antimony sulfide thin film and a preparation method and application thereof, and belongs to the technical field of solar cells. According to the method, the crystallinity of the selenium antimony sulfide crystal film is adjusted through high-intensity magnetic field equipment, deposition of the film and growth of different crystal faces of crystals in the hydrothermal process are adjusted and controlled by placing a hydrothermal reaction kettle in a superconducting magnet and applying a high-intensity magnetic field, and improvement of the crystallinity of the selenium antimony sulfide film and growth of crystal grains are achieved. The method for enhancing the crystallinity of the thin film is safe, reliable and simple in operation process. The selenium antimony sulfide solar cell absorption layer is prepared by adopting high-intensity magnetic field equipment for the first time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar cells, and in particular to an antimony selenide sulfide film and a preparation method and application thereof. Background Art

[0002] Solar energy is a clean energy source, and the use of this clean renewable energy is an important means to solve energy shortages and environmental pollution. Photovoltaic power generation is one of the effective ways to make full use of solar energy. Scientific research shows that in 2100, the world's solar power generation will exceed 60% of the energy supply. Compared with other clean energy sources such as geothermal energy, hydrogen energy, biomass energy, wind energy, etc., solar energy has the advantages of large reserves and little influence from geographical factors, that is, it can be laid and used on a large scale around the world. For photovoltaic power generation, the cost of power generation is a very important consideration and is also the main factor limiting the application of solar cells. At present, the mainstream solar cells are silicon-based solar cells, which dominate the market. Another large-scale production of cadmium telluride solar cells can be used in multiple scenarios and are often used for building integration, but the price is high and contains toxic elements tellurium and cadmium, which poses a risk of environmental pollution. Finding and developing a photovoltaic material with abundant environmental reserves, environmentally friendly, and a high level of photoelectric conversion efficiency of solar cell modules has always been an important topic.

[0003] As an emerging semiconductor material in recent years, antimony selenide sulfide (Sb2(S,Se)3) has the advantages of high extinction coefficient, simple crystal structure, high stability, rich content of constituent elements, and low toxicity. It is a new photovoltaic material with great potential. 5 cm -1 ), the theoretical limit efficiency is >32%, and the optical band gap is adjustable at 1.1-1.7eV, which is conducive to making full use of solar energy; in addition, the special quasi-one-dimensional characteristics also make it have huge development potential as a photovoltaic material, so this material has received widespread attention. With the efforts of many research groups at home and abroad, various preparation methods have been developed, including solution method, evaporation method, vapor transport deposition (VTD), near-space sublimation method and hydrothermal method, and the conversion efficiency is also steadily improving. Among them, solar cells made of antimony selenium sulfide material have achieved an efficiency of more than 10%. At present, the crystallization quality of antimony selenium sulfide film is far behind other more mature technologies. By improving the crystallinity of the film, high-quality solar devices can be obtained. Summary of the invention

[0004] The purpose of the present invention is to provide an antimony selenide sulfide film and a preparation method and application thereof, so as to solve the technical problem of how to improve the crystallinity of the film and improve the quality of solar energy devices.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing an antimony selenide sulfide film, comprising the following steps:

[0007] 1) Immersing the FTO substrate with the CdS film in a precursor solution, performing a hydrothermal reaction and a magnetic field treatment simultaneously in a closed environment, and obtaining an antimony selenide sulfide precursor film after drying;

[0008] 2) annealing the antimony selenide sulfide precursor film to obtain an antimony selenide sulfide thin film;

[0009] The precursor solution comprises potassium antimony tartrate, sodium thiosulfate and selenourea;

[0010] The magnetic field intensity of the magnetic field treatment is 2-12T.

[0011] Furthermore, the magnetic field rising rate of the magnetic field treatment is 0.1-0.2 T / min.

[0012] Furthermore, the temperature of the hydrothermal reaction is 120-150°C, and the heating rate of the hydrothermal reaction is 5-10°C / min;

[0013] The time of the hydrothermal reaction and the time of the magnetic field treatment are independently 60 to 240 minutes.

[0014] Furthermore, the annealing temperature is 350-380° C., and the annealing time is 5-15 min.

[0015] Furthermore, the molar ratio of potassium antimony tartrate, sodium thiosulfate and selenourea is 1:7-8:0.4-0.5, and the dosage ratio of water and potassium antimony tartrate in the precursor solution is 40 mL:0.2-0.3 g.

[0016] Furthermore, the thickness of the CdS film is 60 to 75 nm;

[0017] The thickness of the antimony selenide sulfide film is 150-260 nm.

[0018] The invention also provides an antimony selenide sulfide film.

[0019] The present invention also provides an application of an antimony selenide sulfide film in a solar cell device. The solar cell device comprises a cathode, an electron transport layer, a light absorption layer, a hole transport layer and an anode. The antimony selenide sulfide film is the light absorption layer in the solar cell device.

[0020] Furthermore, the method for preparing the solar cell device comprises the following steps:

[0021] Spin-coat the Spiro-OMeTAD layer on the antimony selenide sulfide film;

[0022] Gold electrodes were deposited on the Spiro-OMeTAD layer by thermal evaporation.

[0023] Furthermore, the thickness of the Spiro-OMeTAD layer is 60-80 nm, and the thickness of the gold electrode is 60-70 nm.

[0024] Beneficial effects of the present invention:

[0025] The present invention is based on the antimony selenium sulfide film prepared by the hydrothermal method, and uses a strong magnetic field to affect the chemical changes and deposition process in the hydrothermal process, so that the grain orientation of the film changes, the (hk1) orientation of the film is strengthened, the half-peak width of the main crystal plane is reduced, and the crystallinity of the film is effectively improved. The magnetic field affects the deposition process, so that the grain size becomes larger and the number of grain boundary defects is reduced. The method for enhancing the crystallinity of the film provided by the present invention is safe and reliable, and the operation process is simple. The present invention uses a strong magnetic field device for the first time to prepare the absorption layer of the antimony selenium sulfide solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a diagram showing the position of the cadmium sulfide film placed in the reactor;

[0027] Figure 2 The SEM image of the solar cell device obtained in Comparative Application Example 1;

[0028] Figure 3 This is a SEM image of the solar cell device obtained in Application Example 1;

[0029] Figure 4 This is a SEM image of the solar cell device obtained in Application Example 2;

[0030] Figure 5 This is a SEM image of the solar cell device obtained in Application Example 3;

[0031] Figure 6 For comparison with Application Example 1, the XRD patterns of the solar cell devices obtained in Application Examples 1 to 3;

[0032] Figure 7 This is a SEM image of the solar cell device obtained in Application Example 4;

[0033] Figure 8 This is a SEM image of the solar cell device obtained in Application Example 5;

[0034] Fig. 9 For comparison with Application Example 1, the XRD patterns of the solar cell devices obtained in Application Examples 1, 4, and 5;

[0035] Fig.10This is a current density-voltage curve of the solar cell device obtained in Application Example 1. DETAILED DESCRIPTION

[0036] The present invention provides a method for preparing an antimony selenide sulfide film, comprising the following steps:

[0037] 1) Immersing the FTO substrate with the CdS film in a precursor solution, performing a hydrothermal reaction and a magnetic field treatment simultaneously in a closed environment, and obtaining an antimony selenide sulfide precursor film after drying;

[0038] 2) annealing the antimony selenide sulfide precursor film to obtain an antimony selenide sulfide thin film;

[0039] The precursor solution comprises potassium antimony tartrate, sodium thiosulfate and selenourea;

[0040] The magnetic field intensity of the magnetic field treatment is 2-12T.

[0041] In the present invention, the magnetic field intensity of the magnetic field treatment is preferably 4 to 10T, and more preferably 6 to 8T.

[0042] In the present invention, the magnet in the magnetic field treatment is preferably a superconducting magnet, and more preferably a superconducting magnet that can generate a vertical magnetic field.

[0043] In the present invention, the magnetic field rising rate of the magnetic field treatment is 0.1 to 0.2 T / min, preferably 0.12 to 0.18 T / min, and more preferably 0.14 to 0.16 T / min.

[0044] In the present invention, the temperature of the hydrothermal reaction is 120-150°C, preferably 125-145°C, and more preferably 135°C; the heating rate of the hydrothermal reaction is 5-10°C / min, preferably 6-9°C / min, and more preferably 7-8°C / min;

[0045] The time of the hydrothermal reaction and the time of the magnetic field treatment are independently 60 to 240 minutes, preferably 80 to 200 minutes, and more preferably 100 to 180 minutes.

[0046] In the present invention, the annealing temperature is 350-380° C., preferably 375° C.; the annealing time is 5-15 min, preferably 10 min.

[0047] In the present invention, the molar ratio of potassium antimony tartrate, sodium thiosulfate and selenourea is 1:7-8:0.4-0.5, preferably 1:7.2-7.8:0.42-0.48, and further preferably 1:7.4-7.6:0.44-0.46; the dosage ratio of water and potassium antimony tartrate in the precursor solution is 40 mL:0.2-0.3 g, preferably 40 mL:0.2671 g.

[0048] In the present invention, the thickness of the CdS film is 60 to 75 nm, preferably 65 to 70 nm, and more preferably 68 nm.

[0049] In the present invention, the thickness of the antimony selenide sulfide film is 150 to 260 nm, preferably 180 to 240 nm.

[0050] The invention also provides an antimony selenide sulfide film.

[0051] The present invention also provides an application of an antimony selenide sulfide film in a solar cell device. The solar cell device comprises a cathode, an electron transport layer, a light absorption layer, a hole transport layer and an anode. The antimony selenide sulfide film is the light absorption layer in the solar cell device.

[0052] In the present invention, the method for preparing the solar cell device comprises the following steps:

[0053] Spin-coat the Spiro-OMeTAD layer on the antimony selenide sulfide film;

[0054] Gold electrodes were deposited on the Spiro-OMeTAD layer by thermal evaporation.

[0055] In the present invention, the thickness of the Spiro-OMeTAD layer is 60 to 80 nm, preferably 65 to 75 nm; the thickness of the gold electrode is 60 to 70 nm, preferably 62 to 68 nm, and more preferably 64 to 66 nm.

[0056] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0057] Example 1

[0058] The FTO substrate with cadmium sulfide film is fixed on the support frame and placed in a Teflon liner for standby use. 0.2671g potassium antimony tartrate is mixed with 40mL ultrapure water and stirred. After the solid is completely dissolved, 0.7942g sodium thiosulfate is added, and stirring is continued until the solid is completely dissolved. 25mg selenourea is added, and stirring is continued until the solid is completely dissolved. Then the solution is poured into the Teflon liner prepared in advance, and the liner is placed in the reactor matched with it, and the seal is tightened. Then the reactor is placed in the heating jacket, and then the heating jacket is placed in the magnet. The hydrothermal reaction and magnetic field treatment are carried out simultaneously, and the heating rate is set to 7℃ / min, the magnetic field rise rate is 0.15T / min, the insulation time is 180min, the insulation temperature is 135℃, and the magnetic field strength is 10T. After the reaction is completed, the antimony selenide sulfide film is taken out, rinsed with ultrapure water and ethanol, and then blown dry with nitrogen, and then placed in a nitrogen atmosphere for annealing at 375℃ for 10min to obtain an antimony selenide sulfide film under magnetic field control.

[0059] Example 2

[0060] The difference from Example 1 is that the final magnetic field intensity is 5 T, and other conditions are the same as those in Example 1.

[0061] Example 3

[0062] The difference from Example 1 is that the final magnetic field strength is 2T, and other conditions are the same as those in Example 1.

[0063] Example 4

[0064] The difference from Example 1 is that the heat preservation time is 120 minutes, and other conditions are the same as those in Example 1.

[0065] Example 5

[0066] The difference from Example 1 is that the heat preservation time is 240 minutes, and other conditions are the same as those in Example 1.

[0067] Comparative Example 1

[0068] The difference from Example 1 is that the heat preservation time is 120 minutes, and no magnetic field is applied. Other conditions are the same as those in Example 1.

[0069] Application Example 1

[0070] Preparation of solar cell devices:

[0071] (1) FTO pretreatment: FTO was ultrasonically cleaned for 40 min using glass cleaner, ultrapure water, isopropanol, acetone, and anhydrous ethanol, respectively, and then dried with nitrogen and cleaned with a UV-ozone cleaner for 30 min;

[0072] (2) CdS thin film was deposited on FTO by chemical water bath method, and the film thickness was 65 nm;

[0073] (3) Using the method of Example 1, an antimony selenide sulfide film is grown on the substrate with the CdS film, and the film thickness is 240 nm.

[0074] (4) Spin coating a Spiro-OMeTAD layer on the antimony selenide sulfide film at a spin coating speed of 3000 r / min for 30 s. The thickness of the Spiro-OMeTAD layer is 70 nm.

[0075] (5) A gold electrode with a thickness of 65 nm was deposited on the Spiro-OMeTAD layer using thermal evaporation technology.

[0076] Application Example 2

[0077] The difference from Application Example 1 is that the method of Example 2 is adopted to grow an antimony selenide sulfide film with a film thickness of 200 nm.

[0078] Application Example 3

[0079] The difference from Application Example 1 is that the method of Example 3 is adopted to grow an antimony selenide sulfide film with a film thickness of 180 nm.

[0080] Application Example 4

[0081] The difference from Application Example 1 is that the method of Example 4 is adopted to grow an antimony selenide sulfide film with a film thickness of 150 nm.

[0082] Application Example 5

[0083] The difference from Application Example 1 is that the method of Example 5 is adopted to grow an antimony selenide sulfide film with a film thickness of 245 nm.

[0084] Comparative application example 1

[0085] The difference from Application Example 1 is that: the method of Comparative Example 1 is adopted to grow an antimony selenide sulfide film with a film thickness of 350 nm.

[0086] It can be seen from the above embodiments that the present invention provides an antimony selenide sulfide film and a preparation method and application thereof. The present invention adjusts the crystallinity of the antimony selenide sulfide crystal film by a strong magnetic field device, and by placing a hydrothermal reactor in a superconducting magnet and applying a strong magnetic field, the deposition of the film and the growth of different crystal faces of the crystal during the hydrothermal process are regulated, thereby achieving the improvement of the crystallinity of the antimony selenide sulfide film and the growth of the grains.

[0087] Depend on Figures 1 to 10 It can be seen that Figure 1For the growth of antimony selenide sulfide film, attach the FTO glass sheet with CdS film to the glass strip and place it in a Teflon liner at an angle of 60° to 70°. Pour the precursor solution, heat to 135°C and keep it warm for 2 hours to obtain the antimony selenide sulfide film. Figure 2 , Figure 3 , Figure 4 A control group shows the changes in film growth state and grain size under the same growth time and different magnetic field strength changes. Figure 2 , Figure 7 , Figure 8 A control group is shown, which shows the changes in the growth state and grain size of the film under different growth times and the same magnetic field changes. Figure 6 for Figure 2 , Figure 3 , Figure 4 , Figure 5 XRD analysis shows that the crystallinity of the film improves with the increase of magnetic field intensity. Fig. 9 for Figure 2 , Figure 3 , Figure 7 , Figure 8 XRD analysis shows that the crystallinity of the film is improved to a certain extent with the extension of growth time. Fig.10 This is the JV curve of the champion device.

[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an antimony selenide sulfide thin film, characterized in that: The following steps are involved: 1) Immersing the FTO substrate with the CdS film in a precursor solution, performing a hydrothermal reaction and a magnetic field treatment simultaneously in a closed environment, and obtaining an antimony selenide sulfide precursor film after drying; 2) annealing the antimony selenide sulfide precursor film to obtain an antimony selenide sulfide thin film; The precursor solution comprises potassium antimony tartrate, sodium thiosulfate and selenourea; The magnetic field intensity of the magnetic field treatment is 2-12T.

2. The method for preparing an antimony selenide sulfide thin film according to claim 1, characterized in that: The magnetic field rising rate of the magnetic field treatment is 0.1-0.2 T / min.

3. The method for preparing an antimony selenide sulfide thin film according to claim 1 or 2, characterized in that: The temperature of the hydrothermal reaction is 120-150°C, and the heating rate of the hydrothermal reaction is 5-10°C / min; The time of the hydrothermal reaction and the time of the magnetic field treatment are independently 60 to 240 minutes.

4. The method for preparing an antimony selenide sulfide thin film according to claim 3, characterized in that: The annealing temperature is 350-380° C., and the annealing time is 5-15 minutes.

5. The method for preparing an antimony selenide sulfide thin film according to claim 1, 2 or 4, characterized in that: The molar ratio of potassium antimony tartrate, sodium thiosulfate and selenourea is 1:7-8:0.4-0.5, and the dosage ratio of water and potassium antimony tartrate in the precursor solution is 40 mL:0.2-0.3 g.

6. The method for preparing an antimony selenide sulfide thin film according to claim 5, characterized in that: The thickness of the CdS film is 60-75 nm; The thickness of the antimony selenide sulfide film is 150-260 nm.

7. Antimony selenide sulfide thin film prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the antimony selenide sulfide film according to claim 7 in a solar cell device, characterized in that: The solar cell device comprises a cathode, an electron transport layer, a light absorption layer, a hole transport layer and an anode, and the antimony selenium sulfide film is the light absorption layer in the solar cell device.

9. The use of the antimony selenide sulfide thin film in a solar cell device according to claim 8, characterized in that: The method for preparing the solar cell device comprises the following steps: Spin-coat the Spiro-OMeTAD layer on the antimony selenide sulfide film; Gold electrodes were deposited on the Spiro-OMeTAD layer by thermal evaporation.

10. Use of the antimony selenide sulfide thin film in a solar cell device according to claim 8 or 9, characterized in that: The thickness of the Spiro-OMeTAD layer is 60-80 nm, and the thickness of the gold electrode is 60-70 nm.